Effect of Sustainable Glass Powder on the Properties of Reactive Powder Concrete with Polypropylene Fibers - Ali Hussain, Z.; Aljalawi, N. (Engineering, Technology & Applied Science Research, 2022)
Global warming and environmental damage have become major problems. The production of Portland cement releases large quantities of gas, which cause pollution to the atmosphere. This problem can be solved via the use of sustainable materials, such as glass powder. This study investigates the effect of partial replacement of cement with sustainable glass powder at various percentages (0, 15, 20, and 25%) by weight of cement on some mechanical properties (compressive strength, flexural strength, absorption, and dry density) of Reactive Powder Concrete (RPC) containing a percentage of Polypropylene fibers (PRPC) of 1% by weight. Furthermore, steam curing was performed for 5 hours at 90oC after hardening the sample directly. The RPC was designed using local cement, silica fume, and super plasticizer with a water/cement ratio of 0.2 to achieve a compressive strength of 96.3MPa at the age of 28 days, and it was tested at percentages of sustainable glass powder replacement of 0 and 20% by weight of cement. According to the study’s findings, RPC’s compressive strength rose up to 4.2% as a consequence of the use of sustainable glass powder replacement by 20%, flexural strength up to 15.3%, dry density up to 0.49%, and absorption reduction by 31.7% at the age of 28 days and in comparison with the reference mixture.